Retention of hybrid-abutment-crowns with offset implant placement: influence of Crown materials and Ti-base height - Ahmed Alseddiek; Walid Al-Zordk; Ahmed Attia (BMC, 2023)
Abstract Background The purpose of the current study was to assess the impact of three esthetic CAD/CAM material, titanium base height and their interaction on the retention strength of a hybrid-abutment-crown. Methods A total of 42 hybrid-abutment crowns with identical external geometries were designed in CAD software to fit two different Ti-Base abutment heights (n = 42/abutment height): either short (S) with 4 mm (n = 21) or long (L) 7 mm (n = 21) height. Each main group was divided into 3 subgroups (n = 7), according to esthetic crown material, Zirconia (Z), Lithium disilicate (L) and Hybrid ceramic (V). A universal primer and an adhesive resin cement were used for bonding according to the manufacturer instructions. Artificial aging in form of water storage (30 days), chewing simulation (50,000-cycles, 49 N, 1.67 Hz) and thermal cyclic (5000 cycles at 5-55 °C) were applied, specimens were pulled-out under tension load in (N) using a universal testing machine. Two and one-way ANOVA and Post Hoc Tukey test were used for statistical analysis. Results Long lithium disilicate (LL) group showed the highest retention (738.7 ± 178.5) followed by short lithium disilicate (LS) group (688.6 ± 169.9). Meanwhile, short zirconia (ZS) showed the lowest retention strength (231.1 ± 86.9). Conclusion CAD/CAM fabricated lithium disilicate hybrid-abutment-crown can be used instead of conventional crowns over implant abutment. Etchable ceramics are recommended as a material of choice for CAD/CAM fabricated hybrid-abutment-crowns instead of zirconia in terms of retention durability.